Accessibility and innovation: IEB Minecraft as a tool for collection exploration - Pedro B. de Meneses Bolle (Revista do Instituto de Estudos Brasileiros)
ABSTRACT The Instituto de Estudos Brasileiros (IEB) has designed a video game in which playerscreate their own characters and enter the institution’s building to playfully explore the collections distributed among the Archives, the Library and the Visual Arts Collection. The aim of the launch of IEB Minecraft is to promote the Institute to a new audience - with an estimated age between 12 and 20 years old -, already accustomed to using the digital language and the world of games, becoming an innovative way to provide young people with access to the IEB collections playfully and interactively. The collections chosen for the game highlight themes related to the lives and work of Afro-Brazilian individuals and Black history - including intellectuals, artists, and poets - in all their diverse forms of expression.